FENOMENA ALIH ORIENTASI PEMANFAATAN LAHAN HUTAN DI LERENG GUNUNG MURIA - Banowati, Eva (Faculty of Social Science, Universitas Negeri Semarang, 2009)
This study aims to identify the orientation of the phenomenon over land use on the slopes ofÃ‚Â Muria Volcano factor cause and effect and its impact. The sample includes a sample area of researchÃ‚Â Gesengan(village) Ã‚Â and the sample of 80 respondents those determined by random technique. ResearchÃ‚Â variables include education, land ownership and control, superior agricultural commodities. Ways ofÃ‚Â collecting data through interviews, surveys with questionnaires to respondents and several local leaders.Ã‚Â Data processing in this article with Descriptive Percentage. The results showed that the educational levelÃ‚Â of respondents on average low at 6-8 years of successful education means between 6 years old (elementaryÃ‚Â school graduation) to 8 years (or class two on junior ). Citizen who have owned 4 ha or much of landÃ‚Â just 2.50% or only 2 people, most (75%) or 60 people have land under 0.5 ha. Ã¢â‚¬ËœBorganÃ¢â‚¬â„¢ Mastery is overÃ‚Â provisions of the management quota of 0.5 ha. by 31 Ã¢â‚¬ËœpesanggemÃ¢â‚¬â„¢ or 26,25%, the largest acquisitionÃ‚Â there are 2 people or 2.25%. Cassava (manioc) is a superior commodity in Ã‚Â the land Ã‚Â by most Ã¢â‚¬ËœborganÃ¢â‚¬â„¢ orÃ‚Â 85.25% (71 people), only 6 respondents or 7.50% that cultivating maize and cassava in one area, and 3Ã‚Â people that cultivating corn. Most of Ã¢â‚¬ËœPesangemÃ¢â‚¬â„¢ chose cassava as a crop interrupters because can givingÃ‚Â some benefts include: 1) cassava more easily even without treatment, 2) low production costs, - 3) priceÃ‚Â stability; 4) marketable due. Cassava is the raw material for tapioca four industry that is operating aroundÃ‚Â that area.Keywords: Over orientation, borgan, usefull